Monitoring Lan User Wirelessly By Android Mobile Based On Client/Server Mode." (International Journal of Engineering and Computer Science, 2018)
We can use android phone for monitor the network. .We can control very easily network when it is present inside the office and it is very difficult to control when present outside the office. Admin can monitor his WLAN network through his android phone with GUI from remote location, it is an alternative solution for monitor network. The main aim of this android application is to provide all the essential information of the wireless network to the admin on their android phone with the help of Wi-Fi. We are using data connectivity or Wi-Fi to connect the mobile phone to WLAN server. The interaction between the clients and the remote administrator is achieved via a central monitoring server. The main ob jective is to provide maximum details about the network to the administrator on their android phones, when administrator is away from office or goes out station.Keywords: WLAN, Monitoring, Android  Mobile Phone.